Skills in Cognitive Behaviour Counselling and Psychotherapy - Wills Frank (Sage, 2010)
A practical guide to the core techniques used when working with clients in a range of therapeutic settings. Foreword, Introduction, Cognitive Behavior Skills and Their Underpinning Knowledge Base, Assessment and Formulation and Beginning CBT, Using Interpersonal Skills in CBT, Skills for Working with Negative Thoughts, Skills for Working on Changing Behavior, Skills for Working with Emotions in CBT, Skills for Working with Enduring Negative Patterns, Developing CBT: A Perspective of Engagement and Life-Long Learning, Appendices, Guide to the Website Accompanying this Biik, Resources for CBT Measures, Other Cognitive Methods Using Cost-Benefit Analysis and Pie Charts, References, Index.